Prevalence Of Hepatitis-B and Hepatitis-C In Blood Donors of Southern Punjab and The Level of Their Liver Function - Rehman, Madiha; Islam, Nasir; Ejaz, Maryam; Anwar, Sidra; Jan, Fauzia; Zafar, Beenish (Journal of Neonatal Surgery, 2025)
Objectives: The main objectives of this study were to assess the prevalence of hepatic infection (HBsAg and anti-HCV) in blood donor of Nishtar Hospital, Multan, to evaluate the effectiveness of techniques for the detection of HBsAg and anti-HCV and to find the level of liver function in persons found positive and negative for Hepatitis-B and C. Materials and Methods: Study Design: Cross sectional study Study Setting: Blood bank of Nishtar Hospital, Multan Study Duration: From January to December 2024. Data Collection and Analysis: A total of 6865 blood donors (males: 6528 Females: 337) who visited the blood bank of Nishtar Hospital, Multan for blood donations during the year 2024 were included in the study. The data on blood donors referred from various wards of Nishtar Hospital to blood bank was collected. Record of Hepatitis-B antigen (HBsAg), Hepatitis-C antibodies (Anti HCV) and levels of LFT markers was also maintained for comparison between different groups of the study. The blood donors referred to blood bank were divided into three groups depending on the presence or absence of hepatitis markers. Results: A total of 6865 blood donors (males: 6528 Females: 337) who visited the blood bank of Nishtar Hospital, Multan for blood donations during last one year were included in the study. The mean age of these persons was 44.4±7.6 years (range: 18-55). The average anti-HCV positive rate was 0.62% (29/4562), which was 1.07% in the rural population, compared to 0.22% in the urban population. The anti-HCV positivity rate in the 40–59-year age group was higher than in those aged <40 years. History of blood transfusion and transmission in families were the main risk factors for HCV infection in this area. The analysis of the records of blood donors showed that most of them belonged to B+(45.8%) and then A+ (27.2%). Out of 6865 blood donors, 323 (4.7%) were found positive for HBsAg. whereas 327 (4.8%) were found positive for HCV infection. The incidence of HBV and HCV in males and females was approximately equal. Conclusion: We conclude that the incidence of HBs and HCV is very high in general population of southern Punjab. This shows that the screening procedure for HBS and HCV adapted by blood bank is not very efficient and gives many false negative results.